Rancang Bangun Sistem Pelayanan Kantor Wali Nagari Talang Berbasis Web - Syed Abdul Qadir; Muhammad Adri (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2022)
The office of the Wali Nagari Talang is one of the offices engaged in the government department in Gunung Talang District. The Talang Wali Nagari Office carries out the service process for submitting letters needed by the community by visiting the office and bringing the requirements in accordance with the letter requirements requested. With the development of information technology today is so broad and fast, the use of information technology in an agency is very important, even in an era like today almost all jobs use technology to facilitate the process of public service. Along with the development of information technology, the Office of the Wali Nagari Talang at least has an information system to provide services for filing letters, filing letters, and managing population data. The system to be built uses the prototype method where the stages are analyzing requirements, making designs, testing systems, and evaluating systems. This system is also designed using Use Case Diagrams, Activity Diagrams, and Class Diagrams, Entity Relationship Diagrams and using several programming languages, namely HTML, PHP, CSS using the Laravel framework, MySQL as a DBMS (Database Management System) and Sublime Text as a text editor. . The results of this system will produce a system that can apply for letters anywhere and anytime, archive letters, and manage population data in Nagari Talang. Keywords: Information System, Service, Prototype, PHP, MySQL, Laravel